Endoscopic Endonasal total Removal of a Suprasellar, Preinfundibular Retro Chiasmatic Craniopharyngioma: A Surgical Case Report - Alfieri, Alessandra; Rapanà, Armando; Caranci, Ferdinando (Archives of Case Reports, 2024)
Craniopharyngiomas are benign tumors (WHO Grade I), seen in children and adults. Because of their location, they can require challenging clinical and surgical management. In fact, often, because of the presence of calcifications, of a capsule very strongly adherent to neurovascular structures, of the relationship with hypophysis, pituitary stalk, chiasm, carotids, the circle of Willis, basilar artery, and third ventricle, risk of mortality and morbidity is still mandatory. Various surgical techniques have been proposed: transcranial, transsphenoidal, and supraorbital approaches for surgical resection and treatment of craniopharyngiomas. Still, there is no common consent, but often the endonasal transsphenoidal extended procedures are considered the gold standard in many cases. We present a surgical technique of a case of complete surgical removal of an infundibular and retro chiasmatic craniopharyngioma, via an endoscopic endonasal transphenoidal transplanum approach.